The reality of the practice of transformational leadership behavior and its relation to organizational learning in the secondary schools in the governorate of Bisha - Al-Hadil, Abdullah Menahi Saad (Journal of Educational and Psychological Sciences, 2018)
The objective of the study was to uncover the reality of the practice of transformational leadership behavior and organizational learning in the secondary schools in the governorate of Bisha from the point of view of school principals and teachers, as well as to determine the relationship between the practice of transformational leadership behavior and organizational learning. To achieve these objectives, (506) teachers and teachers, including (30) managers and (476) teachers, while the questionnaire consisted of (31) paragraphs were distributedThe second topic dealt with the reality of organizational learning. The results showed that the reality of secondary school principals' conduct of transformational leadership behavior came to a high degree. The practice of secondary school administrations for the reality of organizational learning came to a degree And the existence of a positive positive correlation relationship with mean significance at the level of (0.01) between the practice of transformational leadership behavior and organizational learning. This means that principals' behavior of transformational leadership behavior contributes to enhancing and improving the level of organizational learning Schools breached, the study recommended that the exercise of leadership Transformational behavior, and work to raise organizational learning at the school level, and create a school environment that contribute to the adoption and activation of new initiatives and improved.
Keywords: transformational leadership behavior; organizational learning